2022
DOI: 10.3390/ijerph19063242
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Mental Health Literacy among Young Adolescents in Malaysia

Abstract: Mental health literacy (MHL) is an established multifaceted concept that comprises mental health knowledge, help-seeking, and stigma. Adequate MHL (i.e., the ability to correctly recognize mental health disorders alongside having the intention to seek help) is able improve mental health outcomes among individuals. This study aims to examine the determinants of MHL among young Malaysian adolescents. A cross-sectional study was conducted among 1400 adolescents between 13 and 14 years old from nine national secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…Research on MHL reported that males’ scores are lower than females’ [ 21 ], probably due to the prevailing gender role for males, i.e., the traditional masculine stereotype, rejecting any type of help and avoiding to disclose a personal mental health problem [ 25 ]. With the advancement of age, individuals tend to gain more knowledge and exposure to mental health issues, which might increase their level of MHL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on MHL reported that males’ scores are lower than females’ [ 21 ], probably due to the prevailing gender role for males, i.e., the traditional masculine stereotype, rejecting any type of help and avoiding to disclose a personal mental health problem [ 25 ]. With the advancement of age, individuals tend to gain more knowledge and exposure to mental health issues, which might increase their level of MHL.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, low revenues correspond to limited MHL. This might be explained by a poor parental education level with negative attitudes toward the mentally ill [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A measure proposed to solve this problematic issue was the intervention of the university in the psychological care of students through telemedicine [ 11 ]. With regard to the mental health of students, there are also studies that were conducted before the epidemiological context [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This perceived behavior is defined as Mental Health Literacy (MHL). Although little discussed in Brazil, MHL has been emerging in health promotion, mainly in view of the vulnerability related to mental health imposed in the pandemic context (7) .…”
Section: Introductionmentioning
confidence: 99%